INFLUÊNCIA DA COMPOSIÇÃO DOS NANOFIOS PT-IR/C NA ATIVIDADE CATALÍTICA FRENTE A OXIDAÇÃO ELETROQUÍMICA DE ETANOL EM MEIO ÁCIDO - Almeida,Gláucia R. O. (2020)
Carbon-supported platinum-iridium nanowire-shape electrocatalysts containing 20% of metallic loading were synthesized by chemical reduction method using formic acid as a reducing agent and tested towards the oxidation of ethanol in acidic medium. The developed electrocatalysts were synthesized with the following compositions: Pt0.9Ir0.1/C, Pt0.8Ir0.2/C, Pt0.7Ir0.3/C, Pt0.6Ir0.4/C and Pt0.5Ir0.5/C using for comparison the commercial Pt/C Alfa Aesar catalyst. Physico-chemical characterization was performed using X-ray diffraction (XRD), transmission electron microscopy (TEM), and X-ray fluorescence (XRF, for chemical composition) techniques. All the nanowires present a face-centered cubic crystalline structure of the platinum with modifications in the lattice parameter due to the inclusion of iridium. The XRF analyzes show that the theoretical compositions of the synthesized catalysts are very close to the experimental nominal values. TEM analyses showed the formation of nanowires by the synthesis method used. The electrochemical results on the oxidation of ethanol show that the addition of a second metal to the platinum in the composition of the nanowires increases the catalytic activity of the electrode. The nanowire catalysts with low Ir content (Pt0.9Ir0.1/C, Pt0.8Ir0.2/C, Pt0.7Ir0.3/C) present the best outcomes under the analyzed conditions and are promising for application as anodes in direct ethanol fuel cells.